Study on Chetan Bhagat’s Novels as a Commercial Fiction: Examining the Impact of Chetan Bhagat's Novels on Indian English Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The 'Novel' as a scholarly wonder is new to India. Epics, Lyrics, Dramas, Short Stories and Fables have their good lineages, returning by a few centuries, yet it is amid time of minimal over a century that the novel, the since quite a while ago continued bit of exposition fiction has happened and flourished in India. Among the new young writers the most capable, is maybe Chetan Bhagat. With his novels, Five Point Someone What not to do at IIT (2004), One Night the Call Center (2005), The 3 Mistakes of My Life (2008), 2 States – the Story of My Marriage (2009), Revolution 2020 (2011), What Young India Wants (2012) and Half Girlfriend (2014), Chetan Bhagat has without any assistance reshaped the Indian English novels. Chetan Bhagat is a standout amongst the most perused fiction writers in Indian writing in English. He has composed six novels and one genuine taking all things together. His books have been sold in millions. Postmodern subjects are the major topical worries of his fictions like youth desires, love, sex, marriage, corruption, politics, education and certain different issues identified with urban working class society. In this article, we studied about Chetan Bhagat’s Novels as a Commercial Fiction.